DEVELOPING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT BY USING DIRECT READING -THINKING ACTIVITY STRATEGY - Soraya, Ria; Marbun, Rismaya; Sumarni, Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to investigate the effectiveness of the use of DR-TA strategy to develop the students’ reading comprehension of narrative texts. This research was conducted at SMP Haruniyah Pontianak. The subject of this research was 35 students of the eighth grade. In completing the research, the writer provided the observation checklist and field note to get the data from classroom activities. Besides, this research also used test (objectives test) to measure the students’ reading comprehension achievement in every cycle of treatment. To conduct this research the writer applied two cycles; cycle 1 and 2. There were only 59% of students who achieve the minimum level achievement (MLA) 70 (seventy) in cycle 1. In this case, the use of DR-TA strategy was focused on the students’ way to predict and to think what the students read before concluding the text. As a result, the students’ reading comprehension achievement of narrative text has indicated the increase from the average scores of reading comprehension in two cycles (cycle 1 and cycle 2). The students’ average scores who achieved minimum level achievement (MLA) 59% in cycle 1 and 85.7% in cycle 2. From these results, this research indicated that the use of DR-TA strategy in developing the students’ reading comprehension achievement of narrative was effective in teaching and learning process. Keywords: Reading Comprehension, DR-TA Strategy, Narrative Text